Lasertherapie in der Augenheilkunde – ein Update - Schaub, Friederike; Enders, Philip; Fauser, Sascha (Augenheilkunde up2date, 2018)
Die retinale Photokoagulation stellt auch heute eine Therapieoption bei zahlreichen Netzhauterkrankungen dar. Dieser Beitrag soll die Frage klären, wann heute noch gelasert wird, und den Lesern einen Überblick über die typischen Indikationen und Therapiekonzepte der retinalen Photokoagulation geben sowie aktuelle Entwicklungen und Empfehlungen zusammenfassen.Laser therapy is an important treatment option in retinal diseases, especially in cases of vascular involvement. Most approaches are based on coagulation of retinal structures. As there is increasing use of agents targetting vascular endothelial growth factor in the treatment of macular diseases, indications for the use of laser treatment need to be reviewed carefully, especially with respect to their significance in first line therapy. This article explains recent strategies and treatment protocols. Retinal laser therapy is still widely used within retinal ophthalmology and covers a large spectrum of indications. Despite the success of medical approaches, retinal laser therapy remains an indispensable treatment option for proliferative diabetic retinopathy, central or peripheral vein occlusion and less frequent pathologies, such as retinopathy of prematurity or Coatsʼs disease.
Keywords: Laserkoagulation; proliferative diabetische Retinopathie; Zentralvenenverschluss; navigierte Lasertechnologie; Mikropulsdiodenlaser; Retinopathia praematurorum